Developing Policies and Proposals for Alleviating Key Binding Constraints To Agriculture in The Caribbean: workshop Proceedings Final Report - Inter-American Institute for Cooperation on Agriculture (Inter-American Institute for Cooperation on Agriculture, 2005)
This initiative seeks to facilitate agriculture’s decisive move from the crossroads that it currently finds itself into bold action to reposition its industries, enterprises and peoples along a path of sustainable and equitable growth.